AP-2-Dependent Endocytic Recycling of the Chitin Synthase Chs3 Regulates Polarized Growth in Candida albicans - H. C. Knafler (American Society for Microbiology, 2019)
ABSTRACT The human fungal pathogen Candida albicans is known to require endocytosis to enable its adaptation to diverse niches and to maintain its highly polarized hyphal growth phase. While studies have identified changes in transcription leading to the synthesis and secretion of new proteins to facilitate hyphal growth, effective maintenance of hyphae also requires concomitant removal or relocalization of other cell surface molecules. The key molecules which must be removed from the cell surface, and the mechanisms behind this, have, however, remained elusive. In this study, we show that the AP-2 endocytic adaptor complex is required for the internalization of the major cell wall biosynthesis enzyme Chs3. We demonstrate that this interaction is mediated by the AP-2 mu subunit (Apm4) YXXΦ binding domain. We also show that in the absence of Chs3 recycling via AP-2, cells have abnormal cell wall composition, defective polarized cell wall deposition, and morphological defects. The study also highlights key distinctions between endocytic requirements of growth at yeast buds compared to that at hyphal tips and different requirements of AP-2 in maintaining the polarity of mannosylated proteins and ergosterol at hyphal tips. Together, our findings highlight the importance of correct cell wall deposition in cell shape maintenance and polarized growth and the key regulatory role of endocytic recycling via the AP-2 complex. IMPORTANCE Candida albicans is a human commensal yeast that can cause significant morbidity and mortality in immunocompromised individuals. Within humans, C. albicans can adopt different morphologies as yeast or filamentous hyphae and can occupy different niches with distinct temperatures, pHs, CO2 levels, and nutrient availability. Both morphological switching and growth in different environments require cell surface remodelling, which involves both the addition of newly synthesized proteins as well as the removal of other proteins. In our study, we demonstrate the importance of an adaptor complex AP-2 in internalizing and recycling a specific cell surface enzyme to maintain effective polarized hyphal growth. Defects in formation of the complex or in its ability to interact directly with cargo inhibit enzyme uptake and lead to defective cell walls and aberrant hyphal morphology. Our data indicate that the AP-2 adaptor plays a central role in regulating cell surface composition in Candida.